Targeting TTK Inhibits Tumorigenesis of T‐Cell Lymphoma Through Dephosphorylating p38α and Activating AMPK/mTOR Pathway - Bingyu Liu; Tiange Lu; Mengfei Ding; Xiaoli Zhou; Yujie Jiang; Juanjuan Shang; Wenyue Sun; Shunfeng Hu; Xin Wang; Xiangxiang Zhou (Advanced Science)
Abstract T‐cell lymphoma (TCL) is a group of non‐Hodgkin's lymphoma with high heterogeneity and unfavorable prognosis. Current standard treatments have demonstrated limited efficacy in improving the outcomes for TCL patients. Therefore, identification of novel drug targets is urgently needed to improve the prognosis of TCL patients. Through multi‐omics analysis, aberrant expression of threonine tyrosine kinase (TTK) in TCL is identified. High expression of TTK is closely associated with poor prognosis in TCL patients. Targeting TTK through gene knockdown exerts anti‐tumor effects in vitro and in vivo, including inhibiting the cell proliferation, inducing G2/M phase arrest, enhancing DNA damage and cell apoptosis. Mechanically, p38α is identified as the potential phosphorylation substrate of TTK through phosphoproteomic quantification and motif prediction. Furthermore, inhibition of TTK suppresses activation of p38α through dephosphorylating it at Thr180/Tyr182, thereby promoting the activation of AMPK/mTOR pathway. In addition, targeting TTK enhances the autophagy in TCL cells through dephosphorylating p38α. CFI‐402257, a specific inhibitor of TTK, is found to exhibit anti‐tumor effects and exerted synergistic efficacy with PI3K inhibitor, Duvelisib, in TCL. The study shows that TTK contributes to the development of TCL by regulating p38α‐mediated AMPK/mTOR pathway. CFI‐402257 is expected to be a promising strategy for TCL treatment.